ECOLOGICAL MODERNIZATION OF THE ECONOMY AS A NECESSARY CONDITION FOR SUSTAINABLE DEVELOPMENT OF SOCIETY (INNOVATIVE ECONOMY, 2020)
Pecheniuk A.V., Pecheniuk A.P. ECOLOGICAL MODERNIZATION OF THE ECONOMY AS A NECESSARY CONDITION FOR SUSTAINABLE DEVELOPMENT OF SOCIETYPurpose. The aim of the article is the investigation of the preconditions for ecologization of production and substantiation of the mechanism of implementation of effective environmental modernization of production in Ukraine.Methodology of research. The theoretical and methodological basis of the research became the fundamental positions of modern economic science and the results of research by scientists in the field of environmental production. In this case, a number of general scientific methods are used: theoretical generalization – to study the historical aspects of the formation and development of environmental modernization of production; analysis and synthesis – in determining the factors that restrain the pace of implementation of the latest ecologically safe technologies in Ukraine; managerial modeling – to develop a set of measures for activation the environmental modernization of production; logical – to justify the advantages that the enterprise obtains by investing resources in high-tech ecologically safe technologies.Findings. The negative effects of anthropogenic impact on the environment were investigated, the prerequisites of environmental stagnation in Ukraine were clarified, the necessity of the development of eco-friendly technologies and the transition to a new production philosophy was substantiated, the complexity and ambiguity of the process of environmental modernization of production were analyzed, historical aspects of the implementation of environmental innovations were revealed, the modern tendencies of ecologization of production, the necessity to achieve the conformity of domestic production with the world ecologist standards is proved generalized principles of construction and implementation of effective national greening program production for sustainable development.Originality. The classification of factors that influence the efficiency of ecological modernization of the economy is improved; the theory of the transition of state environmental protection activities from policy regulation to the creation of a suitable business environment, which would contribute to the implementation of environmental innovations in production, has become further developed.Practical value. The implementation of the proposed package of measures proposed in the publication will allow for the construction of a flexible and effective system of state intervention in the mechanisms of the formation of environmental policy at different levels of management; to increase the competitiveness of domestic producers in the world and regional markets; to substantially increase the share of companies, the main activities of which are environmental business and eco-business; to substantially improve the conditions for attracting eco-investments; to achieve a high level of environmental consciousness of citizens.Key words: ecological modernization; sustainable development; ecologization of production; environmental standards; environmental protection; ecological policy; eco-friendly technologies; environmental risks; innovation activity; competitive advantages.
Keywords: Key words; ecological modernization; sustainable development; ecologization of production; environmental standards; environmental protection; ecological policy; eco-friendly technologies; environmental risks; innovation activity; competitive advantages.